Treatment of time and history in the narration of postmodern literature: Kurt Vonnegut’s slaughterhouse- five, Martin Amis’s time’s arrow and Tim O’Brien’s how to tell a true war story - Akter, Shammee (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2017.